Wildland Weeds: Paper Mulberry, Broussonetia papyrifera - Eric C. Morgan; William A. Overholt (EDIS)
This document discusses the invasive plant species, paper mulberry (Broussonetia papyrifera), detailing its historical significance, ecological impact, and current distribution. Originally used for paper production in ancient China, paper mulberry has become a widespread invasive species, disrupting natural vegetation across various regions, including Florida. The article highlights its ability to colonize disturbed areas, spread through fruits and root systems, and form dense thickets. It also provides identification features and recommendations for managing its spread. The document is part of the UF/IFAS Extension series on invasive plants. Publication date: March 2004.